Multinodular bilateral breast lesions diagnosed as primary breast lymphoma in a young lactating woman - Mohammad Akram; Ruquiya Afrose; Sadaf Hayat; Mohammed Naim (SpringerOpen, 2015)
Primary breast lymphoma (PBL) is a rare neoplasm that constitutes 0.4% of malignant breast lesions and 2% of extranodal lymphomas. It is seldom distinguished preoperatively from other common forms of breast cancer. Here, we report a case of a 30-year-old woman (para 3, gravida 0) who presented with multiple bilateral nodular swellings of the breast for 2-months duration, followed by bilateral axillary lymphadenopathy after 15 days, along with low-grade fever, and generalized weakness. On examination, she was found to have multiple firm nodular mass involving both the right and the left breast, along with multiple, bilateral, matted, axillary lymph nodes. A clinical diagnosis of bilateral breast carcinoma with axillary metastasis was made. Fine needle aspiration cytology of both the breast and axillary lymph node revealed monomorphic population of scattered lymphoid cells with moderate anisonucleosis and one to two prominent nucleoli. A cytological diagnosis of PBL was made, which was subsequently confirmed with histopathology and immunohistochemistry for leukocyte common antigen and CD20. Because PBLs are uncommon malignant lesions and they usually do not have characteristic clinical and imaging findings, fine needle aspiration cytology proves to be a simple, rapid, reliable, and cost-effective procedure for successful diagnosis of PBL.